2013
DOI: 10.4184/asj.2013.7.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Adjacent Segment Degeneration Occurring More than 5 Years after Fusion with Pedicle Screw Fixation for Degenerative Lumbar Spine

Abstract: Study DesignA retrospective study.PurposeWe investigated the risk factors in adjacent segment degeneration (ASD) after more than 5 years of follow-up of lumbar spinal fusion.Overview of LiteratureThere are many concerns regarding ASD followed by lumbar spinal fusion. However, there is a great deal of dispute about the risk factors.MethodsA total of 55 patients who were followed up for more than 5 years after lumbar fusion were observed. Gender, age, residence, fusion method, number of fusion segments and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
1
28
3
2
Order By: Relevance
“…These findings are confirmed by those of Soh et al, 22 who found that the main disadvantages of surgical fusion in degenerative instability are the loss of mobility and curvature with deterioration of sagittal balance, instrumentation failure, and increased transfer of stress to the adjacent movable segments, referred to as "transition syndrome". They conducted a five-year follow-up with patients who had undergone posterior instrumentation surgery, and showed degenerative changes in adjacent segments due to loss of mobility and changes in mechanical load at the fusion site.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings are confirmed by those of Soh et al, 22 who found that the main disadvantages of surgical fusion in degenerative instability are the loss of mobility and curvature with deterioration of sagittal balance, instrumentation failure, and increased transfer of stress to the adjacent movable segments, referred to as "transition syndrome". They conducted a five-year follow-up with patients who had undergone posterior instrumentation surgery, and showed degenerative changes in adjacent segments due to loss of mobility and changes in mechanical load at the fusion site.…”
Section: Discussionsupporting
confidence: 79%
“…The degenerative changes in the adjacent segments included segmental instability, spinal stenosis, intervertebral disc injury, spondylolisthesis, and fractures. 22 A measurement is needed that is sensitive to the initial degenerative changes, therefore quantitative MRI analysis has been developed to capture early disc degeneration. The method introduced by Sobajima measures the surface area and intensity of the signal of the pulpy nucleus in patients with changes with symptoms of adjacent disc degeneration, and the results provide an index for T2-weighted magnetic resonance images, 23 from which a correlation can be drawn between the intensity of the signal in magnetic resonance images (MRI) and the composition and condition of the disc.…”
Section: Discussionmentioning
confidence: 99%
“…Its reported incidence is 5.2-29% [29][30][31]. In our study, radicular symptoms were not observed in any of the patients who underwent PLIF thus MRI was not needed.…”
Section: Discussioncontrasting
confidence: 61%
“…Degenerative changes at the adjacent segments were considered to exist when there were at least two of the following criteria: (1) on standing X-rays, the height of the adjacent disc reduced more than 70 %; (2) displacement more than 3 mm on the X-ray of the sagittal plane of the closest upper or lower segment; (3) segmental instability of more than 15°on the lateral X-rays in flexion and extension [3,19]; (4) segmental stenosis and/ or disc degeneration (grade III according Pfirmann classification [20]) at adjacent level on the follow-up MRI. Overall lumbar measures from the radiographs included lumbar lordosis (L1-L5), pelvic incidence (PI), pelvic tilt (PT) and sacral slope (SS).…”
Section: Methodsmentioning
confidence: 99%